The comparison of the problem solving style and abstract thinking between men undergoing methadone maintenance treatment (MMT) and normal subjects - Tajikzadeh, Ù‘Ù‘Fakhri; Zaree, Fatemeh; Abbasi, Fatemeh (International Journal of Applied Behavioral Sciences, 2017)
Introduction: To projects, substance dependent individuals have problem in thinking. Drug dependence is Chronic and recurrent phenomenon with serious harm to the physical, financial, social and family along. The aim of present study is comparison of the problem solving style and abstract thinking in men undergoing methadone maintenance treatment (MMT) and normal men. Methods: Ex post facto method was used on 60 men undergoing methadone maintenance treatment (MMT) and 60 normal men from addiction treatment clinics in Shiraz who were selected through judgmental convenient sampling. The instrument was the problem solving style questionnaire and the Wisconsin Card Sorting Test. The findings were analyzed through Student t test using SPSS version 21. Results: Result showed that the difference between two groups in approach style and creative problem-solving style, sorting piles and preservative errors. There are no difference between two groups in helplessness, problem-solving control, problem-solving confidence and avoidance style. Conclusion: Data analysis showed that men undergoing methadone maintenance treatment (MMT) have problem in problem solving and the abstract thinking, So clinical psychologists should pay attention cognitive factors in treatment substance dependent individuals.